Prevention of disorders of behavioral reactions in rats using nootropics with sodium valproate - Ivanov A.V. (Medičnì Perspektivi)
Using of anticonvulsants can trigger a number of side effects, such as possible changes in behavior and emotional state of people with epilepsy, risk of unwarranted aggression, nervousness, discoordination, sleepiness, encephalopathies. However, the epilepsy itself as a chronic neurological pathology causes cognitive and "epileptic" deficiency, in patients general retardation, sluggishness of mental activity, decreased cognitive abilities de¬velop. Therefore it is advisable to combine anticonvulsants with nootropics with their ability to protect the brain and increase body's resistance to extreme stress, reduce neurological deficits, restore damaged mnestic and mental functions. The author considered the use of nootropics on the background of anticonvulsant sodium valproate (80 mg/kg). Behavioral reactions of white rats in the test "Open field" and muscle tone of white mice in the test "muscle relaxation" were performed on the day 4 nootropics introduction in 1 hour after a single sodium valproate application. It’s shown experimentally that sodium valproate provided systemic depriming action on orientation and exploratory activity of rats: locomotor activity reduced in the number of squares strolled by 62.8% and in the number of vertical uprights by 80%, the amount of peeping into the burrows decreased by 58.7% as compared with the control. In the test "muscle relaxation" sodium valproate reduced muscle strength of mice by 38.6%. Against the background of anticonvulsant application piracetam (500 mg/kg) had no effect on the behavioral responses of rats and muscle tone of mice. Citicoline (500 mg/kg) increased locomotor activity in the number of squares crossed by 29.7%, in the number of vertical racks – by 20%, and the endurance of mice by 18.6%. Memantine (10 mg/kg) in combination with sodium valproate insignificantly decreased (by 8.4%) locomotor activity of rats, but increased exploratory activity by 30.5%; withholding of mice on the wire prolonged by 33.3% as compared to monotherapy.